Comparative analysis of technical efficiency of piglet farming in three production center provinces in Indonesia - H. Harianto; E. N. Keraru (Diponegoro University, 2022)
Pork production occupies the third position in Indonesia, after chicken and beef. Even pigs occupy the top rank in contributing to Indonesia's live animal exports. The purpose of this study was to com-pare the level of technical efficiency of smallholder piglet production farming in three centers of pig production areas, namely North Sumatra, Bali, and East Nusa Tenggara (NTT). The research data was sourced from secondary data at the farm level, collected by the Central Statistics Agency of Indonesia, through the Livestock Business Household Survey. This research utilized the stochastic production frontier model to assess the production efficiency and the one-step maximum likelihood estimation (MLE) method to measure the level of technical efficiency and the significance of the factors. The re-sults show that the average level of technical efficiency of piglet production farms in Indonesia is rela-tively low. Piglet production farms in Bali have the highest efficiency level and NTT is the lowest of the three provinces being compared. The number of pigs, feed expenditure, capital, and vaccinations are important factors in influencing production and the level of technical efficiency. Public policies that can increase farmers' access to production factors and better pig farm vaccine management become a necessity.